Perancangan Model Tata Kelola Teknologi Informasi Berbasis COBIT Pada Sektor Publik - Agustina, Delima; Sutabri, Tata (TRANSFORMASI, 2025)
The rapid development of information technology (IT) demands that the public sector have good IT governance to support the effectiveness and efficiency of public services. However, many government agencies still face obstacles in measuring and improving IT governance performance. This study aims to design an IT governance model based on the COBIT (Control Objectives for Information and Related Technology) framework that suits the characteristics of the public sector. The method used is a simple survey of 15 respondents of IT employees in several local government agencies, complemented by capability level analysis based on COBIT 2019 domains. The results show that most IT processes are at level 2 (Managed Process), with several areas such as risk management and service management still at level 1 (Performed Process). The resulting model describes the stages of continuous improvement that can be applied to increase IT governance maturity in public agencies.Keywords: COBIT, IT Governance, Public Sector, Capability Level, Governance Model